Performance Evaluation of Check Pointing and Threshold Algorithm for Load Balancing in Cloud Computing - Karki, Sheetal; Goyal, Anshika (International Journal of Computer Sciences and Engineering, 2025)
The cloud computing is practice of using a network of remote servers hosted on the internet to store, manage, and process data, rather than a local server or personal computer, it builds on the idea of using a remote server or infrastructure as a software service. The data that is stored in centralized virtual machine known as cloud and it can be managed by an end user using services provided. Cloud Service Provider (CSP) are designed for giving users the services based on their demands and are to be paid for being served. As there is large number of requests so the load increases, hence a Load balancing is done to reduce the energy consumption and maximize resource utilization. In this paper, the work is based on the task migration when virtual machine gets overloaded at the time of cloudlet execution. The CSPs are responsible to assign tasks to the most appropriate virtual machine for the execution. When any of the virtual machine gets overloaded, the task is migrated from one virtual machine to another or it could be queued which can be decided by the threshold and check pointing algorithm by minimizing the processing time, energy and resource consumption.